Higher education student's attitude towards using gamification and its relation with achievement - Celis, Magna Guerrero (2023)
The aim of this study was to determine the possible relation between higher education students' attitude towards the use of gamification with their academic performance. 'Gamification is using game-based mechanics, aesthetics and game thinking to engage people, motivate action, promote learning, and solve problems' [1, p. 10]. 280 first year university students taking a basic mathematics course participated in the study. Gamification activities were part of the course. Students were asked to answer a survey that measured their attitude towards the gamification activities and a survey that assessed their motivation. Students were also assessed on mathematical achievement. Correlations between the measures were carried out to find out if there is a relationship between their attitude toward these activities, their motivation and their performance. Results show that there was a significant relation between attitude towards gamification activities and student's motivation (r=.92, p<.01), but two correlations between attitude and motivation with their mathematical achievement were found non-significant (r=.04,p=.65;r=.02, p=.76). These results highlight the importance of using new activities like gamification to keep students motivated, but this has no relation with their performance. A future experimental study is needed to assess the impact of these activities on students learning.